Highly Reversible Zn Anode Enabled by Controllable Formation of Nucleation Sites for Zn‐Based Batteries - Liang, Pengcheng; Yi, Jin; Liu, Xiaoyu; Wu, Kai; Wang, Zhuo; Cui, Jin; Liu, Yuyu; Wang, Yonggang; Xia, Yongyao; Zhang, Jiujun (Advanced functional materials, 2020)
Aqueous Zn batteries have drawn tremendous attention for their several advantages. However, the challenges of Zn anodes such as the corrosion and ZnO densification have compromised their application in rechargeable Zn‐based batteries. In this paper, a straightforward strategy is employed to facilitate the uniform Zn stripping/plating of the Zn anode through using a ZrO2 coating layer, which contributes to the controllable nucleation sites for Zn2+ and fast Zn2+ transportation through the favorable Maxwell–Wagner polarization. As a result, the low polarization (24 mV at 0.25 mA cm−2), high Coulombic efficiency (99.36% at 20 mA cm−2), and long cycle life (over 3800 h at 0.25 mA cm−2) can be obtained for the ZrO2‐coated Zn anode. It is believed that the ZrO2 coating layer can also act as an inert physical barrier to decrease the contact of the anode and electrolyte, thus reducing both the Zn corrosion and formation of ZnO densification, and then improve the reversibility of Zn anode. The results demonstrated in this work provide an appealing strategy for the future development of rechargeable Zn‐based batteries. A highly reversible Zn anode is achieved through controllable nucleation sites for Zn2+ and fast Zn2+ transportation under the favorable Maxwell–Wagner polarization, in which a low polarization (24 mV), high Coulombic efficiency (99.36%), and long cycle life (over 3800 h) are obtained by employing a ZrO2‐coating layer.